THE DEVELOPMENT OF A FOURTH-GRADE ENGLISH LEARNING MODULE INTEGRATING SUMBAWA’S LOCAL WISDOM AT SDN BOAK DALAM - Susyyanti Kartini; Aris Dwi Intan Aprianti; Samsudin (GLOBAL: Education Language and Humanity Journal, 2026)
This study aimed to develop a valid and culturally contextualized English language learning module for fourth-grade students (Phase B) in accordance with Indonesia’s Merdeka Curriculum, by integrating local wisdom from Sumbawa. Motivated by the lack of culturally relevant instructional materials and students’ limited exposure to English, the research employed a Research and Development (R&D) method using a modified ADDIE model (Analysis, Design, Development). Data were gathered through teacher interviews, document analysis, and expert validations. The findings from the analysis stage indicated that existing materials lacked local context, leading to vocabulary difficulties, low engagement, and challenges in understanding basic grammar, such as the Present Continuous Tense. The designed module addressed these gaps by embedding Sumbawa cultural elements such as traditional crafts, community activities, and local narratives into English lessons, allowing learners to connect language learning with familiar social practices. Validation by experts and practitioners yielded an average score of 85.7%, indicating that the module was “valid” and appropriate for use, with minor revisions. The study supports theories of contextual and culturally responsive pedagogy, emphasizing the role of local identity in enhancing language comprehension and learner motivation. Practical implications include the module’s potential to be replicated in other culturally diverse and under-resourced educational contexts. The study recommends further field-testing to assess learning outcomes and extend the design model to other English competencies. This work contributes to the growing body of literature advocating for English language instruction that is both globally relevant and locally grounded.